MENENTUKAN ARAH PENERAPAN TEKNIK DAN METODE PENERJEMAHAN ARAB – INDONESIA DALAM TEKS KEAGAMAAN : STUDI KASUS PENERJEMAHAN SYI’RU MACHALLIL QIYĀM KARYA FATIHUDDIN - Muhammad Muslih, Muhammad Yunus Anis (CMES (Center of Middle Eastern Studies), 2017)
This study aims to describe translation techniques and methods used in the translation of Syi‘ru Machallil Qiyām. This research is based on conceptual theories about translation techniques from Molina and Albir and Newmark's theory of translation method. This study is under the research paradigm of descriptive-qualitative. The data were collected by using non-interactive method is, using document recording technique. The data analysis applied the Miles and Huberman’s model (1994) which consists of data reduction, data presentation, and conclusion and verification. The data source was the book of Al-Barzanji authored by Sayyid Ja'far Al-Barzanji which was translated by Yasin (2001). The results showed that there were 10 translation techniques used in the translation of Syi‘ru Machallil Qiyām including the technique of adaptation found 2 data (2.7%), description 4 data (5.5%), generalization of 3 data (4.1%), particularization of 1 data (1.4%), calque found 10 data (13.7% ), literal 12 data (16.4%), borrowings 4 data (5.5%), reduction of 2 data (2.7%), addition of 13 data (17.8%), and shifting of 22 data (30.2% ). The most widely used technique was the shifting technique found as many as 22 data. This was occured primarily due to the underlying difference between the Source Language (SL) and TL structures, therefore, to achieve the language correspondence and acceptability, the translator has focused on using more shifting techniques. The translation method used was oriented at the Target Language (TL) of 49 data (67,1%).